Taxation and the User Cost of Capital: An Introduction - John Creedy; Norman Gemmell (New Zealand Government, The Treasury, 2015)
The aim of this paper is to provide an introduction to the concept of user cost and its determinants. Particular attention is given to the influence of taxation. The concept of user cost relates to the rental, the rate of return to capital, that arises in a profit maximising situation in which further investment in capital produces no additional profit. This paper sets out in some detail the range of assumptions involved in obtaining alternative expressions for the user cost. The user cost refers to a before-tax capital rental, the rate of return that ensures that the (after-tax) cost of capital is equal to the post-tax returns over its life. Hence, associated with the user cost measure is an effective marginal tax rate. This can differ substantially from the statutory marginal rate applicable to the investor. A related effective average tax rate is also defined.
Keywords: 330; Kapitalertragsteuer; Steuervergünstigung; Mietwohnung; Kapitalkosten; Kapitalmarktrendite; Steuertarif; Steuerwirkung; Theorie